Impact of corporate diversification on idiosyncratic volatility. - Liao, Huiyi. (2008)
We analyze a set of firms during 1997 to 2001 and find that corporate diversification is significantly and negatively related to firm-specific volatility. This study provides confirmative evidence that corporate diversification has the benefit of lowering idiosyncratic volatility.